The use of financial derivatives and earnings volatility: evidence from Malaysia - Chua, Yong Xia; Phua, Lian Kee; Lok, Char Lee (2018)
In this turbulent business environment, each and every company will face various types of business risk such as foreign currency risk, interest rate risk, commodity risk and others. As the top management of an organization, managers could not escape from handling such risks when making economic decisions. Therefore, the top management of an organization has the responsibility to eliminate the risks into an acceptable level before embarking into any business transactions. Financial derivatives have been commonly used to hedge an organization’s risk and reducing the probability of the company facing default. The usage of derivatives will directly affect firms’ earnings volatility. Hence, this paper aims at providing evidence on what is the tendency of Malaysian companies in using derivatives as risk management tool. As financial derivatives are used as a risk management tool, it can directly reflect on the companies’ earnings and cash flows. Therefore, in this study, we examine the effect of financial derivatives, director remuneration and board independence on earnings volatility. By using the top 100 non-financial listed companies in Malaysia, multiple regression analysis was conducted on the research model. The results exhibit that 54% of the top 100 Malaysian listed companies use derivatives. While, out of the top 100 listed companies, around 46 companies or 46% of firms are not using derivatives instrument. This shows that the usage of derivatives in Malaysia is not very common. In addition, the results show that the usage of derivatives is negatively related to earnings volatility while the directors’ remuneration and board independence have no significant relationship with earnings volatility. The findings provide empirical evidence that the usage of derivatives can mitigate earnings volatility.